Reproductive health of refugees: barriers to accessing healthcare systems in host countries - Vl.V. Podolsky; V.V. Podolsky; N.V. Medvedovska (Group of Companies Med Expert, LLC, 2023)
Refugees around the world face numerous challenges when it comes to accessing healthcare services, particularly in the area of reproductive health. This narrative review aims to explore the barriers that refugees encounter when trying to access healthcare systems in their host countries. These barriers include language and cultural differences, lack of knowledge about the healthcare system, limited access to transportation, financial constraints, and stigma. Comprehensive healthcare services, including healthcare access, nutrition, and mental health support, are crucial to prevent and manage chronic diseases and improve health outcomes for refugees, particularly those with diabetes who may face restricted availability of medications and monitoring devices. It is essential to ensure refugees diagnosed with diabetes have sufficient access to insulin supplies and equipment to administer it securely. We also highlight the impact of these barriers on the reproductive health of refugees, including inadequate prenatal care, lack of access to contraception and family planning services, and increased risk of sexually transmitted infections. The findings of this review underscore the urgent need for policymakers and healthcare providers to address the unique challenges that refugees face when accessing reproductive healthcare. Efforts must be made to improve access to information, increase cultural competency among healthcare providers, and address financial and transportation barriers. By addressing these challenges, we can ensure that refugees have the necessary support and resources to maintain their reproductive health and well-being. No conflict of interests was declared by the authors.